PRP pre-treatment of the implantation zone improves the survival rate of fat autograft - Ilona Pak; Meirambek Askarov; Dmitriy Klyuyev; Min Sungh Tak; Ulpan Batenova; Dauren Yeskermessov; Yevgeniy Kamyshanskiy (Frontiers in Bioengineering and Biotechnology)
BackgroundLipofilling is gaining in popularity daily as a method of replenishing the volume of almost any part of the human body. However, the use of adipose tissue as a filler has its limitations in the long term, in the form of a low survival rate of the fat graft because of fibrotic replacement and fat cell apoptosis. The aim of this study was a comparative morphological assessment of fat autograft survival in the groups undergoing a standard lipofilling protocol and the pre-implantation treatment of the implantation area with platelet-rich plasma.Material and methodsTwenty-four male Californian rabbits that had undergone hypodermic implantation of a fat autograft in the area of the auricle were used in the study. All cases were classified into three groups depending on the method of platelet-rich plasma treatment. After 3 months (90 days) of exposure, macroscopic and histological examinations of the fat autograft were conducted.ResultsThe volume and histological normality of the fat autograft were statistically significantly preserved in the group with preoperative treatment of the implant area and intraoperative treatment of the autograft compared to the group without it and with intraoperative treatment alone.DiscussionWe have demonstrated that the pre-implantation use of platelet-rich plasma significantly improves the standard intraoperative technique and increases the survival rate of the fat autograft by enhancing angiogenesis, with a decreased degree of hypoxic-ischemic, fibrotic, and inflammatory damage in the implant area.ConclusionThe effect of improved preservation of the morphological pattern of the fat implant during preoperative treatment may be due to a favorable preoperative locoregional stromal-vascular microenvironment with an active perfusion and diffusion potential of the stromal skeleton.